Kajian Hukum Pidana Terhadap Kedudukan Informan Sebagai Saksi Menurut Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika Dengan Undang-Undang Nomor 8 Tahun 1981 Tentang KUHAP - Lainata, Claudio Varly; Pasalbessy, John Dirk; Latupeirissa, Julianus Edwin (Faculty of Law, Universitas Pattimura, 2022)
Introduction: In Indonesia, the law that supervises and controls the use of narcotics as well as overcoming the abuse of narcotics and the treatment of its victims is known as the narcotics law.Purpose of the Research: Therefore, this writing aims to analyze and explain the position of informants in Law 35 of 2009 and the role of informants in helping to reveal narcotics crimes.Methods of the Research: This type of research in the preparation of legal writing is normative legal research. Peter Mahmud Marzuki said that legal research in general is a process to find the rule of law, legal principles, and legal doctrines in order to answer the legal issues at hand. Normative legal research, another name is doctrinal legal research, also known as library research or document study because this research was conducted or aimed only at written regulations.Results of the Research: The results of the study show that legally, narcotics are regulated in Law Number 35 of 2009 concerning Narcotics. However, in this case, informants who are intermediaries in following up narcotics cases are not explicitly regulated in the legislation, only policies that make informants are still used by the police to assist in uncovering narcotics trafficking crimes. The informant contributes to the law enforcement of narcotics crime, where the role of this informant is one of the technical ones in uncovering the crime of narcotics trafficking and this informant does not receive legal protection